Komparasi Kemampuan dan Kemauan Membayar Angkutan Umum Terhadap Biaya Operasional Kendaraan di Bandar Lampung - Astuti, Eka Febri; Sulistyorini, Rahayu; Usman, Kristianto (Jurnal Informasi, Sains dan Teknologi, 2024)
Public transportation has many benefits. However, currently public transportation has not been able to survive in providing its services. Prices and financing are at the heart of the problem of developing public transport. The initial effort to revive public transportation is to find out the ability and willingness of the community to pay for public transportation and compare it to the operational costs incurred by service providers in running their business. The ability to pay is known as Ability to Pay (ATP) and Willingness to Pay (WTP) is explored through analysis of questionnaire data collected using Accidental Simple Random Sampling from the people of Bandar Lampung City aged between 15 and 65 years. The results of the analysis show that the ATP (Rp. 2,824.27/km) and WTP (1,970.92/km) of the people of Bandar Lampung City are still above the applicable tariff (Rp. 300.00/km). Vehicle Operational Costs (BOK) for public transportation cannot yet be covered by fare revenues obtained with an average loading factor (16.45%). For a loading factor of 70%, according to World Bank standards, a tariff of IDR is required Rp 710.23/km to cover vehicle operating costs.